Functional Ultrastructure Atlas of Tissue Biology and Pathology - Pavelka, Margit. (Springer Vienna : Imprint: Springer, 2010)
This atlas of functional ultrastructure provides a detailed insight into the complex structure and organization of cells and tissues, highlights specific cellular and tissue functions, and the dynamics of diverse intracellular processes. Highly informative electron micrographs are complemented by explanatory texts, selected references and schemes. The concept that subcellular organelles provide the structural foundation for fundamental processes of living organisms is emphasized. The first part covers the cellular organelles and changes due to experiments or occurring under pathological conditions. The second part illustrates by selected examples principles of functional tissue organization and typical changes resulting from experimental induction or pathological situations.  .